(untitled) (Contemporary Journal of Social Science Review, 2025)
This research paper aims to study different dialects of Saraki language. Saraiki belt is really vast, and is spread throughout Pakistan. To conduct this research fifteen participants from five different regions were selected. The participants belonged to DG Khan, Multan, Bahawalpur, Rahimyar Khan and Muzaffargarh respectively. A questionnaire was distributed among selected participants based on lexical choices made by them in their specific region. For example, participants from Multan used the word "thall" for desert, while those from Bahawalpur preferred "raet". A mixed method study based on both qualitative and quantitative analysis was done. The results of the study were analyzed using Wiliam Labov’s theoretical framework of variationist sociolinguistics. The findings of the study showed significant lexical differences that corelates with regional boundaries. This study also highlights that the social factors play a vital role in linguistic variation.